If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = 5cos(x + 30) Multiply F * x xF = 5cos(x + 30) Reorder the terms: xF = 5cos(30 + x) xF = (30 * 5cos + x * 5cos) xF = (150cos + 5cosx) Solving xF = 150cos + 5cosx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5cosx' to each side of the equation. -5cosx + xF = 150cos + 5cosx + -5cosx Combine like terms: 5cosx + -5cosx = 0 -5cosx + xF = 150cos + 0 -5cosx + xF = 150cos Reorder the terms: -150cos + -5cosx + xF = 150cos + -150cos Combine like terms: 150cos + -150cos = 0 -150cos + -5cosx + xF = 0 The solution to this equation could not be determined.
| -5x-74-8x=121 | | 3x+-3x+4y+7y=36+30 | | 8x+18=-3(x+5) | | 7x^2-2x=4 | | -x/65 | | 12x-7y= | | -25+4.905x=0 | | -120+4.905x=0 | | 4.905*x^2=120x | | -7-6x+8x=11 | | 2x^2-54x+559=0 | | M^2+12m+15=0 | | M^2+12m+14=0 | | (14p)/(2q) | | 3(ln)x=7.3 | | 3[b-5]=6 | | 3*lnx=7.3 | | 27x=3x^3 | | 4x+2x-45=21 | | 6x+3=11+4x | | 7u+2u=26 | | 5X-1=-(1-2X) | | x/103 | | (3/2)x-1/2=5/6 | | (2x+1)(5-6x)=3x(4x-1) | | -12+7x=18+4x | | (25x^2)+30x+9=0 | | 15-14g=-3-17g | | 6(3-x)-2(4-x)=0 | | 14x-4=9x+1 | | (4x^2)-4x+1=0 | | 9p+7=10p+10 |